Penerapan Expressive Writing Therapy dntuk Menurunkan Tingkat Kecemasan pada Remaja Korban Bullying di SMA N 14 Semarang - Tuti Anggarawati; Rika Fidiarohana (Lembaga Pengembangan Kinerja Dosen, 2024)
Adolescence is a period of transition from childhood to adulthood characterized by accelerated physical, mental, emotional, and social development. At the education level, adolescents will find many new things in their lives. Bullying behavior carried out verbally, which generally attacks in the form of psychological (psychological/mental), is often carried out by students. The impact of bullying victims experiences a variety of disorders including low psychological well-being. Anxiety is one of the symptoms resulting from bullying. Expressive writing therapy is methods to express emotional feelings with the aim of reducing stress experienced. This case study aims to describe the application of expressive writing therapy to reduce anxiety levels in adolescent victims of bullying in high school n 14 Semarang. The research method used descriptive using a case study method. There were 2 subjects according to the inclusion criteria. The instrument used the Depression Axiety Stress Scale (DASS) questionnaire sheet. The results of subject I experiencing a decrease in anxiety levels from 19 (severe) to 14 (moderate). Subject II experienced a decrease in anxiety levels from 16 (severe) to 12 (moderate). The study concluded that expressive writing therapy is proven to reduce anxiety levels..